2017
DOI: 10.3389/fpls.2017.00491
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Investigation of Phelipanche aegyptiaca Reveals Significant Changes during Developmental Stages and in Its Different Organs

Abstract: Phelipanche aegyptiaca Pers. is a root holoparasitic plant considered to be among the most destructive agricultural weeds worldwide. In order to gain more knowledge about the metabolic profile of the parasite during its developmental stages, we carried out primary metabolic and lipid profiling using GC-MS analysis. In addition, the levels of amino acids that incorporate into proteins, total protein in the albumin fraction, nitrogen, reduced sugars, and phenols were determined. For the assays, the whole plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
4
12
1
Order By: Relevance
“…We conclude that P. aegyptiaca and T. versicolor undergo shifts in their metabolite profiles that are more closely related to patterns of parasite development than to influences from host metabolism. This fits nicely with results of a study by Nativ et al [28] of P. aegyptiaca metabolite profiles that spanned stages of development ranging from the tubercle (older than our stage 4.2) to mature shoots, and in organs ranging from roots to flowers. This work showed that the greatest differences in metabolite profiles were between different organs, rather than across time in the same organs.…”
Section: Discussionsupporting
confidence: 92%
“…We conclude that P. aegyptiaca and T. versicolor undergo shifts in their metabolite profiles that are more closely related to patterns of parasite development than to influences from host metabolism. This fits nicely with results of a study by Nativ et al [28] of P. aegyptiaca metabolite profiles that spanned stages of development ranging from the tubercle (older than our stage 4.2) to mature shoots, and in organs ranging from roots to flowers. This work showed that the greatest differences in metabolite profiles were between different organs, rather than across time in the same organs.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with most damage being done to the host plant during post-connection growth stages [1]. Given the findings that carbohydrates accumulate in pre-emergent shoots in P. aegyptiaca [79], it is possible that sugar transporters could be involved in mobilizing the storage of these carbohydrates during the flowering phase.…”
Section: Discussionsupporting
confidence: 78%
“…As shown in the PCA and heatmap analyses, the stems were significantly affected by the host, the haustoria were less affected and the flowers the reproductive organ had relatively the most conserved profile. A similar observation was also derived from the analysis of five different organs of P. aegyptiaca that collected in the same mature stage, showing significant differences in the metabolites' levels between the vegetative and reproductive organs [21]. The main metabolites that accumulated in flowers were the soluble amino acids and sugar acids (except for galactaric acid) (Table 1).…”
Section: Discussionsupporting
confidence: 75%